2000
DOI: 10.1097/00007632-200004150-00015
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Paraspinal Muscle Spindles in Lumbosacral Position Sense in Individuals With and Without Low Back Pain

Abstract: Patients with low back pain have a less refined position sense than healthy individuals, possibly because of an altered paraspinal muscle spindle afference and central processing of this sensory input. Furthermore, muscle vibration can be an interesting expedient for improving proprioception and enhancing local muscle control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
324
4
10

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 418 publications
(346 citation statements)
references
References 44 publications
8
324
4
10
Order By: Relevance
“…Although the knowledge surrounding proprioception is relatively limited because it is such a complex function, several studies have found that proprioceptive deficits in individuals with LBP might contribute to a lack of stability [8,33,34]. Another explanation for decreased balance performance in LBP subjects might be altered muscle function.…”
Section: Discussionmentioning
confidence: 99%
“…Although the knowledge surrounding proprioception is relatively limited because it is such a complex function, several studies have found that proprioceptive deficits in individuals with LBP might contribute to a lack of stability [8,33,34]. Another explanation for decreased balance performance in LBP subjects might be altered muscle function.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, low back pain patients have less lumbar repositioning accuracy (2) and need practice to reach accuracies similar to normal subjects (3). Altered paraspinal muscle spindles and central processing were suggested to be the cause for the less refined position sense in low back pain patients (2). The present study explores the presence of a phenomenon in the lumbar spine that can alter proprioceptive signaling from paraspinal muscle spindles.…”
Section: Introductionmentioning
confidence: 89%
“…For example, a slouched sitting posture alters an individual's ability to accurately reposition their lumbar spine (1). Clinically, low back pain patients have less lumbar repositioning accuracy (2) and need practice to reach accuracies similar to normal subjects (3). Altered paraspinal muscle spindles and central processing were suggested to be the cause for the less refined position sense in low back pain patients (2).…”
Section: Introductionmentioning
confidence: 99%
“…Injury to the spine structures (e.g., joints, ligaments, disc) can disrupt one or more of the spine stability sub‐systems 19, 63, 64, 65. Induced pain studies in humans confirm that local pain of the spinal column leads to reduction of neural drive to the adjacent MF, apparent on functional MRI 66 and ultrasound 67, 68.…”
Section: Introductionmentioning
confidence: 99%